Penerapan Pembelajaran Diferensiasi melalui PBL untuk Meningkatkan Kemampuan Penyajian Data Siswa Kelas VII - Sasa Apriliska; Isyati Radiah (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to improve seventh-grade students' data presentation ability through the implementation of differentiated learning integrated with Problem-Based Learning (PBL) in the form of student worksheets (LKPD). The study employed a Design-Based Research (DBR) approach involving 153 students from five classes at SMP Negeri 17 Mataram. The results indicated an increase in students' average scores from 43.97 to 63.04 after the intervention. Additionally, there was a shift in the distribution of ability categories from low to medium and high. Differentiated learning through PBL proved effective in addressing diverse learning readiness and encouraging active student engagement. Thus, this approach offers an adaptive and contextual strategy to enhance students’ data literacy in mathematics.